Electronic Customer Relationship Management (E-Crm) Pada Rsu Assalam Gemolong - Sutariyani .; Kunto Hamidjoyo; Sara Adelya N - STMIK AUB Surakarta (Indonesian Journal of Networking and Security (IJNS), 2017)
Abstract - RSU Assalam is a private health institution in the field of medical services. Assalam RSU strategy undertaken in order to establish a good communication relationship with the patient is confined to the offline print media and via phone or SMS. This has an impact on the fabric of the communication link between the patients and the hospitals that it is difficult to deliver information to patients, such as information services that are owned, physician practice schedule updated and other info needed patient. For that we need a good business strategy through Customer Relationship Management (CRM) used to acquire new customers, promote service excellence and services, enhance the benefits customers / patients and maintained good relations to customers because customer satisfaction is an important factor in the achievement of objectives company. To realize this strategy should be developed e-CRM application. In this research, a web-based system built using Adobe Dreamweaver as a tool of software development (development tool), the programming language PHP and MySQL as its DBMS. System development method used is waterfall model with the step system needs analysis, system design, writing code, testing methods blackbox, implementation and maintenance. Results of e-CRM is a hospital information services, online registration, patient report card based on the period and the queue of patients. Results of testing the software declare all items on the test and the test class level system testing with blackbox testing techniques represent all of the application's functionality e-CRM is expressed in accordance with the expected results. This indicates that the e-CRM on RSU Assalam has been completed and can be used. Keywords: CRM, e-CRM, business strategy, RSU Assalam Abstrak - RSU Assalam adalah lembaga kesehatan swasta di bidang pelayanan medis. Strategi Assalam RSU dilakukan untuk membangun hubungan komunikasi yang baik dengan pasien hanya terbatas pada media cetak offline dan melalui telepon atau SMS. Hal ini berdampak pada kain link komunikasi antara pasien dan rumah sakit yang sulit untuk menyampaikan informasi kepada pasien, seperti layanan informasi yang dimiliki, jadwal praktek dokter diperbarui dan info yang dibutuhkan pasien lainnya. Untuk itu kita perlu strategi bisnis yang baik melalui Customer Relationship Management (CRM) yang digunakan untuk mengakuisisi pelanggan baru, mempromosikan keunggulan layanan dan jasa, meningkatkan pelanggan manfaat / pasien dan mempertahankan hubungan baik dengan pelanggan karena kepuasan pelanggan merupakan faktor penting dalam pencapaian tujuan perusahaan. Untuk mewujudkan strategi ini harus dikembangkan aplikasi e-CRM. Dalam penelitian ini, sistem berbasis web yang dibangun menggunakan Adobe Dreamweaver sebagai alat pengembangan perangkat lunak (alat pengembangan), bahasa pemrograman PHP dan MySQL sebagai DBMS-nya. Metode pengembangan sistem yang digunakan adalah model air terjun dengan sistem langkah analisis, desain sistem, menulis kode, pengujian metode blackbox, pelaksanaan dan pemeliharaan kebutuhan. Hasil e-CRM adalah layanan informasi rumah sakit, pendaftaran online, pasien rapor berdasarkan periode dan antrian pasien. Hasil dari pengujian perangkat lunak menyatakan semua item pada tes dan pengujian sistem tingkat kelas uji dengan teknik pengujian blackbox mewakili semua aplikasi fungsi e-CRM dinyatakan sesuai dengan hasil yang diharapkan. Hal ini menunjukkan bahwa e-CRM pada RSU Assalam telah selesai dan dapat digunakan. Kata kunci: CRM, e-CRM, strategi bisnis, RSU Assalam